Study on the Radial Displacement Law and Permeability Enhancement Effect of Coal Body around Hydraulic Flushing Drilling. (7th June 2021) - Yang, He; Miao, Dejun; Liu, Zhen; Zhao, Dawei; Zhang, Mingrui
Abstract : Hydraulic flushing drilling technology can not only improve the efficiency of high-pressure and low-permeability geological reservoir coalbed methane drainage but also effectively reduce the probability of coal and gas outburst disasters through pressure relief. The main mechanism of this technology is to expand the borehole diameter through hydraulic flushing measures, increase the strain of the coal around the borehole, and increase the development of cracked pores, to improve the permeability of the coal seam and realize the dual reduction of ground and gas pressure. However, in the actual application process, the interaction mechanism among the stress field, the structure field, and the seepage field is still not clear, and there is no clear method to accurately determine the pressure relief range based on the pressure relief mechanism in order to carry out reasonable drilling arrangements. Therefore, this article comprehensively uses laboratory experiments, numerical simulations, and field practices to fully explain the hydraulic flushing pressure relief mechanism and proposes a method to accurately determine the pressure relief range based on the radial line strain law. The results based on radial line strain showed that the effective relief radius expands to 0.86 m once adopting the Φ 579 mm hydraulic flushing borehole compared to Φ 160 mm; the borehole's equivalent diameter of drilling field #11 is 2 to 3 times than that of #10 and 1.2 times the average CBM extraction amount. Therefore, as the borehole diameter increases, the permeability and radial line strain of the coal around the borehole increase significantly, but the tendency of the increase in permeability decreases with increasing vertical stress. The findings of this study can help for a better understanding of the pressure relief and permeability enhancement mechanism of hydraulic flushing, and the method of determining the pressure relief range based on radial strain can also provide a new way for other mines to practice ideas.